Health-related quality of life in children and adolescents: subjective well being - Gaspar, T.; Ribeiro, J.; Matos, M. G.; Leal, I.; Ferreira, A. I. (The Spanish Journal of Psychology, 2012)
The main objective of this study was to build a model, which includes personal and social factors, that helps to highlight factors that promote health-related quality of Life (HRQoL) in children and in adolescents. A sample of 3195 children and adolescents was acquired from 5th and 7th graders from all five Portuguese regions. In this study three independent latent variables were specified - Physical, Psychological and Social and two dependent latent variables were measured: Health behavior and Quality of Life. The integrative model was composed by different components: (I) health-related quality of life, integrated by 8 dimensions from KIDSCREEN-52; (2) health behavior, (3) variables related to physical health: (4) variables related to social health; (5) variables related to psychological health. As results were found strong correlation between psychological dimensions and self-esteem and other factors and a structural equation model was developed. The model presented a RMSEA index of .08. Similarly, adjustment levels for the CFI. NFI and IFI vary above or around .90, which suggests a good adjustment for the hypothesized model. The model presented significant qui-square. This study showed that in all the samples studied, the psychological variables were those that contributed at a superior level to HRQoL.